Powered endoscopic inferior turbinoplasty: clinical study - Al-Helo, Sajad; Falih, Hasanain; Jumma, Ahmed (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Nasal obstruction is a common complaint in ENT clinics and significantly affect the patient`s quality of life. Inferior turbinate hypertrophy is one of the common causes of nasal obstruction, surgical reduction of inferior turbinate is indicated in refractory cases not responding to conservative measures and the optimal surgical technique is controversial. The aim of the study was to evaluate the clinical outcomes of powered endoscopic inferior turbinoplasty in the management of inferior turbinate hypertrophy. Methods: An interventional study (single group clinical trial) was conducted and powered endoscopic inferior turbinoplasty was performed on 30 patients complaining of chronic nasal obstruction due to inferior turbinate hypertrophy and other causes of nasal obstruction were excluded. Results: Assessed preoperatively and 1st week, 1st month and 3rd month postoperatively depending on subjective visual analogue scale scores for nasal obstruction, endoscopic grading system and complications. There was significant improvement in nasal obstruction and significant reduction in inferior turbinate size and mild complications that completely absent at the third month following the surgery. Conclusions: Microdebrider-assisted inferior turbinoplasty as a safe, effective and reliable alternative method for inferior turbinate reduction.